MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MEWARNAI PADA ANAK KELOMPOK B DI TK AR-RAHMA MUARA BADAK PADA TAHUN AJARAN 2015/2016 - Mariati Mariati; Ika Apriati Widya Puteri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
Maturity of fine motor group B children ie age 5-6 years is very important as the initial capital for writing skills that are needed at the next level of education. With the expected coloring activity expected finger-finger and wrist splinting and good hand coordination can develop the writing skills of children This study aims to determine whether learning through coloring activities can improve fine motor skills in children group B in kindergarten Ar-Rahma Muara Badak in 2015/2016 academic year or not This study was conducted using classroom action research in two cycles. The subjects of this research are students of group B group in Ar-Rahma Muara Badak kindergarten consisting of sixteen children with fine motor ability object. Data collection techniques used are observation and documentation. Data analysis used qualitative and quantitative descriptive. The results showed that the fine motor skills of the child when the pre-action reached the criteria of Expanding Expectancy were two children or 12.5%, in the first cycle increased to Very Good Develops to six children or 37.5% and in cycle two remained on the criteria of Growing Very Good has increased to be a child or 75%. Based on the data it can be concluded that the coloring activity can improve the fine motor skills of children group B Kindergarten Ar-Rahma Muara Badak in the academic year 2015/2016. The increase is inseparable from the learning steps that are: (1) One class is divided into three groups consisting of four to five children (2) Each group gets four to five kinds of dye and crayon media that have been placed in the container (3) examples of coloring activities to be undertaken (4) Conveying agreed rules during coloring activities and (5) The colored drawings are tailored to the ongoing theme in kindergarten. Based on the results of this study it is recommended that educators Early childhood education can use methods in improving the maternal ability of children.